Paracetamol-Induced Glutathione Consumption: Is There a Link With Severe COVID-19 Illness? - Sestili, Piero; Fimognari, Carmela (Frontiers in Pharmacology, 2020)
COVID-19 pandemic is posing an unprecedented sanitary threat: antiviral and host-directed medications to treat the disease are urgently needed. A great effort has been paid to find drugs and treatments for hospitalized, severely ill patients. However, medications used for the domiciliary management of early symptoms, notwithstanding their importance, have not been and are not presently regarded with the same attention and seriousness. In analogy with other airways viral infections, COVID-19 patients in the early phase require specific antivirals (still lacking) and non-etiotropic drugs to lower pain, fever and control inflammation. Non-steroidal antinflammatory drugs (NSAIDs) and paracetamol (PAC) are widely used as non-etiotropic agents in common airways viral infections and hence are both theoretically repurposable for COVID-19. However, a warning from some research reports and National Authorities raised NSAIDs safety concerns because of the supposed induction of ACE2 protein levels (the receptor used by SARS-CoV2 to enter host airways cells), the risk of bacterial superinfections and masking of disease symptoms. As a consequence, the use of NSAIDs was, and is, strongly discouraged while the alternative adoption of paracetamol is still preferred. On the basis of novel data and hypothesis on the possible role of scarce glutathione (GSH) levels in the exacerbation of COVID-19 and of the GSH depleting activity of PAC, this commentary raises the question of whether PAC may be the better choice.